Twenty Years after the NATO Armed Intervention: The Kosovo case and Remedial Secession - Miloš Hrnjaz (Međunarodni Problemi)
The NATO military intervention in Yugoslavia took place twenty years ago, triggering several important consequences not only regarding the Kosovo case but also on the global level. This paper concentrates on the issue of the relevance of the Kosovo Case for the concept of remedial secession. The main argument of the paper is that the Kosovo Case is of the utmost importance for the above concept because it has motivated numerous states to officially accept the existence of remedial secession in international law. Several decades ago, this was hardly imaginable. Even though the Kosovo Case has not motivated states to change the formal sources of international law in this regard, it could change the way international actors behave when they make decisions about secession. Therefore, one of the conclusions of the paper is that, after Kosovo, the genie of remedial secession could not be put back in the bottle.